Acute bottlenecks to the survival of juvenile Pygoscelis penguins occur immediately after fledging - Hinke, Jefferson T. (2020)
Estimating when and where survival bottlenecks occur in free-ranging marine predators is critical for effective demographic monitoring and spatial planning. This is particularly relevant to juvenile stages of long-lived species for which direct observations of death are typically not possible. We used satellite telemetry data from fledgling Adelie, chinstrap and gentoo penguins near the Antarctic Peninsula to estimate the spatio-temporal scale of a bottleneck after fledging. Fledglings were tracked up to 106 days over distances of up to 2140 km. Cumulative losses of tags increased to 73% within 16 days of deployment, followed by an order-of-magnitude reduction in loss rates thereafter. The timing and location of tag losses were consistent with at-sea observations of penguin carcasses and bioenergetics simulations of mass loss to thresholds associated with low recruitment probability. A bootstrapping procedure is used to assess tag loss owing to death versus other factors. Results suggest insensitivity in the timing of the bottleneck and quantify plausible ranges of mortality rates within the bottleneck. The weight of evidence indicates that a survival bottleneck for fledgling penguins is acute, attributable to predation and starvation, and may account for at least 33% of juvenile mortality.